Upaya Pencegahan Untuk Mengurangi Kasus Cyberbullying Di Kalangan Remaja - Evelin Evelita Palilingan; Rachel Dina Olivia Hutabarat; Rick Kevin Pramigoro (Institut Nalanda, 2024)
Cyberbullying has become a major concern in the digital environment of adolescents. This article discusses various preventive measures that can be implemented to reduce cases of cyberbullying among teenagers. Factors such as lack of parental supervision, social pressures, and lack of awareness of its impacts are the primary focus in these prevention efforts. Several preventive steps that can be taken include education and awareness about the dangers of cyberbullying, parental involvement in monitoring children's online activities. Collaboration among various stakeholders such as parents, schools, communities, and social media platforms is crucial in creating a safe and supportive online environment for adolescents.